Analyzing the Availability of TPACK Framework Dimensions Among Elementary Mathematics Teachers: A Survey-Based Study on Demographic Variables - Rakan S. Alqahtani; Essa A. Alibraheim (Education Sciences, 2025)
This study sought to explore the extent to which the dimensions of the TPACK framework are present among mathematics teachers at the elementary level from their perspective. The study’s goals were accomplished through the use of a descriptive approach, and a questionnaire was distributed to 107 mathematics teachers in the eastern region of Saudi Arabia to collect data. The results indicated that the dimensions of the TPACK framework were highly present among the participants. The highest level was observed in the dimension of Pedagogical Content Knowledge (PCK) at 78.1%, while the lowest was in the Technological Content Knowledge (TCK) dimension at 68.2%. The findings also revealed no statistically significant differences based on gender or education sector. However, statistically significant differences were found in favor of teachers with higher academic qualifications (postgraduate studies) and more years of teaching experience. The study recommends continuing efforts to enhance teacher training programs dealing with integrating technology into teaching, drawing on global experiences in applying the TPACK framework.